PROFILE OF SURROGATE MARKERS OF MOLECULAR SUBTYPES USING THE EXPRESSION PATTERN OF ER, PR, AND HER2/NEU RECEPTORS IN OPERABLE BREAST CANCER - VERMA, VISHAL; RN, HIREMATH; BASRA, SHARANJIT SINGH; CHOUREY, NIRAJ; SINHA, POOJA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study was planned with an aim to study the profile of surrogate markers of molecular subtypes using the expression pattern of ER, PR, and HER2/NEU receptors in operable breast cancer so that most effective and advantageous treatment can be offered for better surgical outcomes. Methods: A cross-sectional observational study was carried out in one of the tertiary care centers in Central UP. All patients presenting to the center with early and locally advanced breast cancer with age bracket between 18 and 75 years during 2-year period and willing to participate in the study were included in the sample size. Clinical staging was done using the standard TNM criteria and all the specimens were subjected to immunohistochemical evaluation for surrogate molecular subtyping Results: Out of 94 cases enrolled in the study, a total of 32 (34.4%) were identified as luminal A, 3 (3.2%) were identified as luminal B, 35 (37.6%) were identified as HER2 positive, and remaining 23 (24.7%) were identified as triple negative. Statistically, there was no significant difference among groups with respect to age (p=0.958) and BMI (p=0.332). However, there was a significant difference among groups with respect to clinical stage (p=0.031), clinical nodal involvement (p=0.014), pathological staging (p=0.006), and pathological nodal involvement (p=0.023). Among those with nodal involvement, all the cases had involvement of one node except for one patient in Group I who had involvement of thrMost of the luminal A cases (81.3%) were clinically Stage 1 or 2. All the luminal B cases were clinically Stage 2 or 3 (100%). Almost half (48.8%) of Her2-negative cases were Stage 3 or 4. Majority of triple-negative cases were Stage 3 or 4 (65.2%). Clinically, nodal involvement was seen to be maximum in Her2-negative and triple-negative groups (54.3% and 52.2% of cases, respectively). Pathologically, most of the luminal A (83.9%), Her2 negative (81.8%), and all the luminal B cases were Stage 2. Pathologically, nodal involvement was seen in 16.1% of luminal A, 42.4% of Her2-negative, and 50% of triple-negative cases. Conclusion: The findings of the present study provided a glimpse of expression pattern of ER, PR, and HER2/NEU receptors in operable breast cancer based on which most effective and advantageous treatment can be offered for better surgical outcomes.